2017
DOI: 10.4018/978-1-5225-1054-3.ch010
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Tourism Supply Chains Management and Optimization Models (TSCM – OM)

Abstract: Around the world tourism industry represents economic benefits to the countries in where the tourist attractions are located. The purpose of this chapter is to search and review recent researches related to the area of tourism under supply chain management and optimization models perspectives. The main aim of this chapter is to identify and discuss how the tourism supply chain is studied when it is subject to different economic, market, and optimization strategies. Considering the period of 2005 to 2016, a sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The SC is the processes and activities that unite organisational efforts within a firm to respond to the needs, desires and information that suppliers and customers provide (Cox and Perkins, 2008). SCM is the management of a wide network of relationships inside and outside the firm to achieve customer satisfaction (Avilés-González et al ., 2017). SCM focuses on achieving value for its products by working simultaneously with suppliers, manufacturers, customers and all major stakeholders (Handfield et al.…”
Section: Literature and Hypothesis Developmentmentioning
confidence: 99%
“…The SC is the processes and activities that unite organisational efforts within a firm to respond to the needs, desires and information that suppliers and customers provide (Cox and Perkins, 2008). SCM is the management of a wide network of relationships inside and outside the firm to achieve customer satisfaction (Avilés-González et al ., 2017). SCM focuses on achieving value for its products by working simultaneously with suppliers, manufacturers, customers and all major stakeholders (Handfield et al.…”
Section: Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Their study laid emphasis on understanding cultural dissimilarities of bordering areas and acknowledging the differences through open communication as a way to develop coordination among tourism SC entities. Avilés-González et al (2016) suggested that tourism SC entities, being highly diverse in their operations, should focus on developing coordination mechanisms to enhance flexibility and visibility to enhance responsiveness to customer demands. Accordingly, while such SCs are diverse and complex in managing, research must address such challenging questions targeted at increasing the operating performance at minimal costs.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Further, comparing path estimates of these dominant enablers, it is suggestive that shared vision is deemed to be the most important enabler of TSCA, followed by relationship development, technology perception/response and inter-firm integration. Hence, lodge operators, tour operators and restaurant owners must understand the importance of these enablers and should invest accordingly for improving the above capabilities (Avilés-González et al , 2016). The importance of shared vision must be strengthened so that every tourism SC entity feels the crucial responsibility of exchanging their know-how and plans with other entities for mutual benefits (Jena and Jog, 2016).…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Indeed, supply chain sustainability is one of the important aspects of creating added value for customers [23]. The supply chain is a group or network of interconnected relationships that aim to increase profitability and create added value for customers.…”
Section: Introductionmentioning
confidence: 99%